Study of the Content of Anions in the Pathologic Aqueous Humor by Ionic Capillary Electrophoresis - Ndiaye, Momar; Hadji Amadou Ba, El; Diop, Abdoulaye (Asian Journal of Chemistry, 2013)
In this work, the content of certain anions of cataract affected patients has been determined. The aqueous humor was sampled with a sterile insulin syringe out of an inspiration puncture, at the ophthalmological clinic of Aristide Le Dantec Hospital. The measurements were taken by ionic capillary electrophoresis, which is a sensitive and specific technique of modern analysis. The detection limits for the electrolytes range from 20-84 ppb. The results of the measurements showed the presence of chloride ions (maxima 141.62 mmol/L), nitrate ions (maxima 2.29 mmol/L) and hydrogen phosphate ions (maxima 0.93 mmol/L). Sulfate, chlorate and fluoride ions were also detected, but at a state of traces. The histograms of the Gauss curve made it possible to determine the reference values for the chloride and nitrate ions which present a normal distribution. Concerning the hydrogen phosphate, the average was considered to be a reference value. Besides, the comparison of results with the physiological data of the normal aqueous humor and the plasma shows the role of these ions in the genesis of the crystalline opacification.